Wiley Rutledge, Executive Detention, and Judicial Conscience at War - Craig Green (Washington University Law Review, 2006)
John Ferren’s Salt of the Earth, Conscience of the Court is the first full biography of Rutledge, and the book not only lifts Rutledge from obscurity’s shadow; it also dispels any “limbo” surrounding the Court he served. Part I of this Article offers a brief biographical sketch showing that Rutledge deserves that much. His pre-judicial life as dean, legal reformer, and advocate of progressive politics provides context for his work on the bench. Also, Rutledge’s tale illuminates broader issues, including FDR’s transformative judicial appointments, early twentieth-century legal education, and the New Deal’s influence on both. Students of history, and especially students of the Court, will appreciate Ferren’s introduction to this unknown, important Justice. Part II shifts from the historical to the modern, analyzing the impact of Rutledge’s judicial work on today’s cases concerning executive detention. In recent Supreme Court litigation, President Bush has claimed the power to detain individuals without judicial oversight, without criminal charges, and with at most hand-tailored military commissions to punish violations of the law of nations. Such issues might seem novel today, but they would not to Rutledge. The most important cases of his era concerned the executive’s authority to detain. And Rutledge’s career, more than that of any other judge, exemplifies the challenges and mistakes affecting the rule of law in wartime. Part III connects Rutledge’s life and Ferren’s book to the deepest issues underlying any judicial biography—namely, what judges should do and who they should be. Consider why judicial biographies are read in the first place. Compared to politicians, movie stars, generals, and other “biographees,” judges fill their lives with plodding, sedentary events that do not produce a gripping read. The unacknowledged appeal of judicial biographies, however, is the light that their subjects’ stories cast on general issues of judging and judicial role. In our legal culture, biography is a repository for stories about “great” and “villainous” judges. These stories shape the context of modern judicial performance and, in turn, how such performance is itself judged. In the final analysis, I suggest that judicial biography—done well, at the right time—can focus much-needed attention on questions of judicial role. And although the character and talents of judges are always important, they are distinctively so under the pressures of our War on Terror.
Keywords: Constitutional history; Detention of persons; Japanese Americans – Evacuation & amp; relocation; 1942-1945; Executive power; Rutledge; Wiley Blount